The crosstalk between FGF21 and GH leads to weakened GH receptor signaling and IGF1 expression and is associated with growth failure in very preterm infants - Mistry, Jayna N.; Silvennoinen, Sanna; Zaman, Farasat; Sävendahl, Lars; Mariniello, Katia; Hall, Charlotte; Howard, Sasha R.; Dunkel, Leo; Sankilampi, Ulla; Guasti, Leonardo (Frontiers in Endocrinology, 2023)
Fibroblast growth factor 21 (FGF21) is an essential metabolic regulator that adapts to changes in nutritional status. Severe childhood undernutrition induces elevated FGF21 levels, contributing to growth hormone (GH) resistance and subsequent linear growth attenuation potentially through a direct action on chondrocytes. In this study, we assessed expression of the components of both GH and FGF21 pathways in rare and unique human growth plates obtained from children, showing localization within the proliferative and pre-hypertrophic zones. Moreover, we investigated the mechanistic interplay of FGF21 on GH receptor (GHR) signalling in a heterologous system: chronic FGF21 exposure increased GH-induced GHR turnover and SOCS2 expression, leading to the inhibition of STAT5 phosphorylation and IGF-1 expression. The clinical significance of FGF21 signalling through GH receptors was tested in nutritionally driven growth failure seen in very preterm (VPT) infants right after birth. VPT infants display an immediate linear growth failure after birth followed by growth catch-up. Consistent with the in vitro model data, we show that circulating FGF21 levels were elevated during deflection in linear growth compared to catch-up growth and were inversely correlated with the length velocity and circulating IGF1 levels. This study further supports a central role of FGF21 in GH resistance and linear growth failure and suggests a direct action on the growth plate.